Hyogo framework for action and urban disaster resilience - Matsuoka, Yuki; Shaw, Rajib (Emerald, 2014)
We live in a world which continues to experience dramatic suffering and loss of life due to natural hazards. The disaster paradigm has accelerated efforts towards resilience building, particularly since the adoption of the Hyogo Framework for Action (HFA), a ten year plan to build the resilience of nations and communities to disasters. Urban areas present complexity and interconnectivity of various elements, and this needs to be considered when building the resilience of such areas to disasters. To address urban risks, local level disaster risk reduction (DRR) is of fundamental importance, not only because it is closer to the citizens, but because it is the repository of regulatory governance functions and local knowledge. The need to scale up the capacity of DRR at the local government level to build urban resilience is a key incentive for this study. With particular reference to the example of Makati City in the Philippines, this book analyses a local DRR approach with reference to the HFA, applies a micro-level resilience assessment and discusses an effective model for enhancing local DRR capacity in the future.
Keywords: Hazard mitigation -- Philippines -- Makati.; Emergency management -- Philippines -- Makati.; elektronické knihy; electronic books